THE INFLUENCE OF ARCHIVES SYSTEMS, INFORMATION SYSTEMS AND INFRASTRUCTURE FACILITIES ON THE PERFORMANCE OF DPRD EMPLOYEES IN SOUTH KALIMANTAN PROVINCE - HAMDI, HAMDI (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The problem in this study is whether there is an influence of the filing system, information systems and infrastructure on the performance of employees at the DPRD Province of South Kalimantan. This study aims to find out whether there is an effect of the filing system, information and infrastructure systems on the performance of employees in the DPRD of the Province of South Kalimantan. The population of this study is employees at the DPRD of South Kalimantan Province . This research is a population approach study so the sample of this study is the population itself with 30 respondents. There are four variables studied in this study, namely the filing system (X1), Information systems (X2), and infrastructure (X3), and the performance of Employees at the South Kalimantan Provincial Parliament District ( Y ) . Based on the results of multiple linear regression analysis calculated by using SPSS obtained Y = 19.067 + 0.099X1 + 0.785X2 + 0.812X3 The partial test results were obtained tcount 0.706 and tcount = 8.900 with a significance of 0.000 <0.05 so this means there is influence from each variable is a filing system, information and infrastructure systems on the performance of employees at the DPRD Province of South Kalimantan. Simultaneous test results obtained Fcount of 44.810 with a significance of 0.000 <0.05, this means that there is an effect of the filing system, information systems and infrastructure together on the performance of employees in the DPRD Province of South Kalimantan . The conclusion that partially or simultaneously the filing system, information and infrastructure systems have a positive and significant effect on the performance of employees in the South Kalimantan Provincial DPRD